STANDAR OPERASIONAL PROSEDUR DI BANK SUMSEL BABEL CABANG LAHAT - Ahmad Pramudya; Choiriyah Choiriyah (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2021)
Standard Operating Procedure is a work guide or work method used to carry out the operational activities of an organization or company so that it runs well in accordance with the expected results. Standard Operating Procedure (SOP) is a document related to procedures carried out chronologically to complete a job that aims to obtain the most effective work results from workers at the lowest possible cost. The SOP usually consists of the benefits, when it was created or revised, the method of writing procedures, and is complemented by a flowchart chart at the end.